DETEKSI DINI KANKER SERVIKS DENGAN PEMERIKSAAN SERVIKS DI KELURAHAN BULURAN KENALI KOTA JAMBI TAHUN 2017 - Julaecha Julaecha; Nurfitriani Nurfitriani (Jurnal Abdimas Kesehatan (JAK), 2019)
Cervical cancer is a malignant disease that occurs in the cervik. Course of the disease is preceded by the condition of pre-concerous lesions of the cerviks is the existence of dysplasi/cervical intraepithelial neoplasia (NIS). On each day is expeced to 40-45 new cases and about 20-25 people  die from cervical cancer. Based on those considered very necessary to provide education  on cervical cancer in women of reproductive age in the prevention of cervical cancer prevention effort.Target outcomes expected are: there is an increased knowledge an increase in knowledge between before and after extension and capable of early detection of cancer  serviks increase. Implementation method to provide counseling.The results  showed that there was important of mother’s interest in doing pap smears examination before and after counseling.